Combination immunosuppressant therapy for rapidly progressive pyoderma gangrenosum in a child. (2nd January 2021) - Kawabe, Shinji; Iwata, Naomi; Nishida, Emi; Kohagura, Toaki; Abe, Naoki; Nakaseko, Haruna; Morita, Akimichi
Abstract: An 8-year-old girl was presented to our clinic with fever, arthritis in her left knee, a necrotic right fifth toe, and multiple large deep-seated ulcerations. She was diagnosed with pyoderma gangrenosum. Treatment with corticosteroids alone was ineffective for her skin lesions, and therefore combination immunosuppressant therapy was administered. Her skin lesions rapidly improved, enabling discontinuation of the corticosteroid therapy and avoiding systemic infection through the ulcers. Combination immunosuppressant therapy may be a treatment option for patients with severe, rapidly progressive pyoderma gangrenosum.